Archaeology and Myth in Early Medieval Europe: Making the Gods of Early Ireland. Issue 1 (2nd January 2020) - Gleeson, Patrick
Abstract : THIS ARTICLE CRITICALLY EXAMINES medieval 1 archaeology's relationship with myth. A surge of research examining pre-Christian belief has seen mythology, place names and folklore increasingly utilised to reconstruct mentalities and cosmologies. As a wider global phenomenon, this trend comes with pitfalls that must be addressed more systematically. This article examines these issues through early medieval Ireland, beginning with an overview of recent trends in cognate disciplines, before proceeding through case studies of Tara, Brú na Bóinne (both Co Meath), and Nenagh (Co Tipperary). Far from being relics of prehistoric cult practices, many deities populating these landscapes may have been consciously invented for political, allegorical and exegetical reasons during the medieval period. This creative process had a marked 8th-century monumental dimension, contemporary with the floruit of saga literature. This precludes such evidence being utilised to reconstruct pre-Christian cosmologies. This has broad implications for research across European medieval archaeology that would seek to access ritual, belief and religion.